2015
DOI: 10.1016/j.ejcdt.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Study of the relationship of dyspnea with depression and functional status in patients with interstitial lung disease

Abstract: Background: Interstitial lung disease (ILD) is a chronic progressive disease resulting in substantial morbidity and mortality. The cardinal symptom of ILD is dyspnea; however, other pulmonary and extra-pulmonary symptoms are often present. Depression is a common comorbidity of many chronic diseases and directly impacts quality of life.Aim of work: To determine the relationship of dyspnea with selected clinical and psychiatric variables including functional status and depression in patients with ILD.Patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Similar to previous studies, our study also showed that except for FEV1% predicted and FEV1/FVC%, psychological distress had a significant relationship with severity of dyspnea and duration of symptoms, arterial oxygen saturation, FVC, and 6-MWD in ILD patients [7,31,32]. The lack of statistically significant correlation of psychological distress with the FEV1/FVC% was because this ratio was either normal or more than normal in ILD patients.…”
Section: Scales (Meansupporting
confidence: 89%
“…Similar to previous studies, our study also showed that except for FEV1% predicted and FEV1/FVC%, psychological distress had a significant relationship with severity of dyspnea and duration of symptoms, arterial oxygen saturation, FVC, and 6-MWD in ILD patients [7,31,32]. The lack of statistically significant correlation of psychological distress with the FEV1/FVC% was because this ratio was either normal or more than normal in ILD patients.…”
Section: Scales (Meansupporting
confidence: 89%